2016 49th Hawaii International Conference on System Sciences (HICSS) 2016
DOI: 10.1109/hicss.2016.481
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Online Dating: What Do We Know So Far? A Systematic Literature Review

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 59 publications
4
37
0
4
Order By: Relevance
“…Similarly, [1] found that men were more likely than women to use Tinder for casual sex. This is in line with evolutionary psychological studies of online dating [4] and of gender differences in social network use [6]. In addition to cultural factors, a successful evolutionary explanation of sex differences in self-presentation generally is the sexual strategies theory of Buss and Schmitt [7].…”
Section: Introduction and Hypothesessupporting
confidence: 57%
See 2 more Smart Citations
“…Similarly, [1] found that men were more likely than women to use Tinder for casual sex. This is in line with evolutionary psychological studies of online dating [4] and of gender differences in social network use [6]. In addition to cultural factors, a successful evolutionary explanation of sex differences in self-presentation generally is the sexual strategies theory of Buss and Schmitt [7].…”
Section: Introduction and Hypothesessupporting
confidence: 57%
“…H1 was not supported: we found no significant difference between numbers of photos uploaded by women and men, with the trend even being in the opposite direction to the prediction. This is in contrast to studies of other social media such as Facebook in which female users typically upload many more photos than male users [4]. This discrepancy may be because Tinder initially asks users to upload a maximum of only six photos when they register with the app.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Unfortunately, we do not have comparable data from adults in the general population. Subscribing to online dating sites attracts such sexual demands from men, who report being more interested in sexual relationships, while women subscribers are more interested in long-term romantic relationships (Abramova, Baumann, Krasnova, & Buxmann, 2016;Netimperative, 2012). It is unclear whether our subjects were aware of the risks associated with online dating (Baumgartner et al, 2010;Couch, Liamputtong, & Pitts, 2012), but other studies report that the risk of being alone is perceived as greater than the risk of deceit or disappointment by people with ID and their caretakers (Löfgren-Mårtenson, 2008;Löfgren-Mårtenson et al, 2015;Seale, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In online dating, there are significant gender differences in terms of attribute preference, self-presentation and interaction [47]. Users usually have a certain preference for mates' age or height.…”
Section: Attribute Difference Distributionmentioning
confidence: 99%